2017
DOI: 10.1111/joop.12190
|View full text |Cite
|
Sign up to set email alerts
|

Empowering public service workers to face bystander conflict: Enhancing resources through a training intervention

Abstract: Public service employees work in occupations that are accompanied with high psychosocial risks. Police, firefighters, and paramedics are increasingly being confronted with argumentative, conflicting bystanders that frustrate them in executing their task. We developed a resource-enhancement intervention and tested its usefulness for securing employees' effective functioning and well-being in bystander conflict. In a simulation-based pre-test post-test control group design, paramedics in the intervention conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 72 publications
1
10
0
2
Order By: Relevance
“…Other role-play scenarios may involve practicing skills for approaching frustrated or agitated patients, family members, and other bystanders who may hinder the care process. van Erp and colleagues (2018) show that participating in such role-play exercises significantly increased paramedics’ confidence and skills for dealing with violence and aggression while preserving employees’ well-being and job dedication.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Other role-play scenarios may involve practicing skills for approaching frustrated or agitated patients, family members, and other bystanders who may hinder the care process. van Erp and colleagues (2018) show that participating in such role-play exercises significantly increased paramedics’ confidence and skills for dealing with violence and aggression while preserving employees’ well-being and job dedication.…”
Section: Resultsmentioning
confidence: 97%
“…Research on team training has shown benefits of training as a team in team processes and team performance (Delise, Allen Gorman, Brooks, Rentsch, & Steele-Johnson, 2010; Hughes et al, 2016), also for dealing specifically with instances of violence and aggression (van Erp et al, 2018). Team 3 therefore recommends the implementation of team training.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another risk factor in paramedicine is vicarious trauma -the work necessitates proximity to life-threatening injuries, illnesses and death, sometimes on a mass scale and often with a patient's family or other bystanders watching triage and treatment efforts (eg, Brady, 2015;Clompus and Albarran, 2016). Paramedics are also commonly the targets of violence from patients and their families and bystandersincluding intimidation, sexual harassment, verbal, physical and sexual assault (eg, Corman, 2017;Maguire et al, 2018;van Erp et al, 2018). Taylor et al (2016: 156) suggest male paramedics especially may under-report such violence for fear of appearing weak.…”
Section: Paramedicine As An 'Extreme' Occupationmentioning
confidence: 99%
“…The most recent example at the time of writing is new legislation enabling paramedics patient's family or other bystanders watching triage and treatment efforts (eg, Brady, 2015;Clompus and Albarran, 2016). Paramedics are also commonly the targets of violence from patients and their families and bystandersincluding intimidation, sexual harassment, verbal, physical and sexual assault (eg, Corman, 2017;Maguire et al, 2018;van Erp et al, 2018). Taylor et al (2016: 156) suggest male paramedics especially may under-report such violence for fear of appearing weak.…”
Section: Introductionmentioning
confidence: 99%